Harmonizing Loss Accounting with Local Cultural and Religious Principles - Mohamad, Anwar Thalib; Paputungan , Vindi; Monantun, Widy Pratiwi; Ismail, Ulvarien; Damiti , Fatmawaty (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research aims to construct loss accounting practices by